An Exploration of the Interaction Between Touch Avoidance and the Pleasant Touch (C-Tactile Afferent) System. (January 2017) - Hielscher, Emily; Mahar, Doug
C-tactile (CT) afferent fibers are optimally stimulated by slow gentle stroking, and an inverted U-shaped relationship exists between stroking velocity and pleasantness ratings of this type of touch. This study investigated whether an additional and potentially important variable, touch avoidance, interacts with this relationship. While a typical U-shaped velocity–pleasantness relationship was expected, those high in touch avoidance were expected to rate CT-targeted touch (1–10 cm/s) as less pleasant than those low in touch avoidance. Thirty-five participants rated the pleasantness of a brush stroked across their forearm at five velocities (0.3, 1, 3, 10, 30 cm/s) administered by a custom-built touch stimulator ("the touch device"). Participants also completed two self-report measures of touch avoidance. There was an inverted U-shaped relationship between velocity and pleasantness ratings, and high touch avoidance resulted in a downward shift of this curve. The downward shift was across all velocities, including those that do not maximally engage CT afferents. It appears that touch avoidance reduces the pleasantness of all kinds of touch in a similar way, and it is unlikely to be specifically related to CT afferent functioning. Other potential mechanisms leading to touch avoidance are discussed.